Effect of Platelet Transfusions on Extracorporeal Life Support Oxygenator’s Function - Chegondi, Madhuradhar; Vijayakumar, Niranjan; Badheka, Aditya; Karam, Oliver (Frontiers in Pediatrics, 2022)
Objective: Bleeding is a common complication of extracorporeal membrane oxygenation (ECMO), leading to increased mortality. Since one of its main complications is bleeding, platelet transfusions are frequently prescribed for children on ECMO. However, there is currently very little information on the effect of platelet transfusions on the function of the ECMO oxygenator. Our objective was to describe the effect of platelet transfusions on oxygenator function. Methods: In this retrospective study, we included all children (< 18 years) who received ECMO support in our pediatric intensive care unit (PICU) between January 2017 and December 2019. Oxygenator function, measured before and after platelet transfusion, was assessed by post-oxygenator PECMOO2 and the gradient in pre- post-oxygenator pressures (Delta Pressure). Results: Over 3 years, we analyzed 235 platelet transfusions from 55 children who received ECMO support. Thirty-two (80%) of children were on veno-arterial ECMO and majority of them were peripherally cannulated. When looking at all transfusions, the post-transfusion change in delta-pressure was 0.1mmHg (p=0.69) and post-membrane PECMOO2 was 6 mmHg (p=0.49). However, in the subgroup with the lowest quartile of pre-transfusion oxygenator function, the post-transfusion change in delta-pressure was -5.2±2.7 mmHg (p<0.001) and the post-transfusion change in PECMOO2 was -118±49 (p<0.001). The area under the ROC curve for the pre-transfusion delta-pressure and PECMOO2 to predict a worsening of the oxygenator function were 0.72 (95%CI 0.63-0.81) and 0.71 (95%CI 0.64-0.78) respectively. Using regression models, pre-transfusion delta-pressure and PECMOO2 were the only independent factors associated with oxygenator function worsening (p<0.001). Conclusions: Our study suggests that overall, platelet transfusions do not seem to impact the ECMO oxygenator’s function. However, in the subgroup of patients with the lowest pre-transfusion oxygenator function, platelet transfusions were independently associated with a worsening function. Future studies should investigate if this warrants adjustments of the anticoagulation strategy around the platelet transfusion, especially among patients with lower oxygenator function.